Computed tomography diagnostic reference levels for adult brain, chest and abdominal examinations: A systematic review. Issue 2 (May 2021) - Garba, I.; Zarb, F.; McEntee, M.F.; Fabri, S.G.
Abstract: Objectives: Radiation dose variation within and among Computed Tomography (CT) centres is commonly reported. This work systematically reviewed published articles on adult Diagnostic Reference Levels (DRLs) for the brain, chest and abdomen to determine the causes and extent of variation. A systematic literature search and review was performed in selected databases containing leading journals in radiography, radiology and medical physics using carefully defined search terms related to CT and DRLs. The quality of the included articles was determined using the Effective Public Health Practise Project tool for quantitative studies. Key findings: The 54 articles reviewed include: 45 studies using human data, 8 studies using phantom data, and one study with both human and phantom data. The main comparator in between studies was the dose indices used in reporting DRLs. DRL variations of up to a factor of 2 for the same procedure were noted in phantom studies, and up to a factor of 3 in human studies. Sources of variation include the type of scanner, the age of the scanner, differences in protocols, variations in patients, as well as variations in study design. Different combinations of dose indices were reported: volume computed tomography dose index (CTDIvol) and dose length product (DLP) (59%); DLP only (11%); weighted computed tomography dose index (CTDIw) and DLP (9%); CTDIvol only (7%); CTDIvol, DLP and effective dose (ED) (6%); CTDIw only (4%); CTDIvol, DLP and size specific dose estimate (SSDE) (1%) and CTDIw, CTDIvol and DLP (1%). The use of different dose indices limited dose comparison between studies. Conclusion: The study noted a 2–3 fold variation in DRLs between studies for the same procedure. The causes of variation are reported and include study design, scanner technology and the use of different dose indices. Implications for practice: There is a need for standardisation of CT DRLs in line with the International Commission on Radiological Protection recommendations to reduce dose variation and facilitate dose comparison.